The importance of a training program on active aging from the perspective of elderly individuals - Maria Gorete Mendonça Reis; Maria Vitória Casas-Novas; Isaura Serra; Maria Dulce Domingues Cabral Magalhães; Luís Manuel Mota Sousa (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to assess the results of a training program focused on the well-being of elderly individuals from the perspective of users, through the opinion on the program impact on their active aging. Methods: a qualitative research, carried out from an intentional sample, consisting of 10 elderly women. Interview conducted by focus group, recorded and transcribed, which constituted the corpus of analysis. Lexical analysis of textual data was performed using the Alceste software. Results: from the analysis, three classes emerged: 1) Health-Activity; 2) Activity-Expectation; 3) Mind-Body Unit. The Activity-Expectation class stands out. Conclusions: the research revealed that elderly individuals consider it important to have expectation, which results in satisfaction and involvement with life as well as the ability to remain active in a perspective of mind-body unit. Future projects should focus on enhancing mental and physical functions to promote active and healthy aging.